The Royal Navy and the German threat 1901 - 1914 ; admiralty plans to protect British trade in a war against Germany - Seligmann, Matthew S. 1967- (Oxford Univ. Press, 2012)
When and why did the Royal Navy come to view the expansion of German maritime power as a threat to British maritime security? Contrary to current thinking, Matthew S. Seligmann argues that Germany emerged as a major threat at the outset of the twentieth century, not because of its growing battle fleet, but because the British Admiralty (rightly) believed that Germany's naval planners intended to arm their country's fast merchant vessels in wartime and send them out to attack British trade in the manner of the privateers of old. This threat to British seaborne commerce was so serious that the leadership of the Royal Navy spent twelve years trying to work out how best to counter it. Ever more elaborate measures were devised to this end
Keywords: Geschichte 1901-1914; Marinepolitik; Deutschland; Großbritannien